2021
DOI: 10.1016/j.xkme.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Live SARS-CoV-2 Shedding in a Maintenance Dialysis Patient

Abstract: Each author contributed important intellectual content during manuscript drafting or revision and accepts accountability for the overall work by ensuring that questions pertaining to the accuracy or integrity of any portion of the work are appropriately investigated and resolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
3
9
0
Order By: Relevance
“…These findings are consistent with other publications specific to the outpatient dialysis population (4 6,11) that illustrate the frequency of persistently positive RT-PCR results after recovery and highlight the challenge of using RT-PCRs as a marker of infectivity. Small observational studies involving patients with ESKD on maintenance dialysis with SARS-CoV-2 infection reported persistent viral RNA detected by RT-PCR 19–40 days from an initial positive test (5,6,11).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with other publications specific to the outpatient dialysis population (4 6,11) that illustrate the frequency of persistently positive RT-PCR results after recovery and highlight the challenge of using RT-PCRs as a marker of infectivity. Small observational studies involving patients with ESKD on maintenance dialysis with SARS-CoV-2 infection reported persistent viral RNA detected by RT-PCR 19–40 days from an initial positive test (5,6,11).…”
Section: Discussionsupporting
confidence: 91%
“…Small observational studies involving patients with ESKD on maintenance dialysis with SARS-CoV-2 infection reported persistent viral RNA detected by RT-PCR 19–40 days from an initial positive test (5,6,11). However, to our knowledge, only Lacson et al (4) performed viral culture to assess infectivity. In 45 specimens with positive SARS-CoV-2 molecular tests from 29 patients on in-center hemodialysis who were followed weekly after diagnosis, only two patients had positive viral cultures (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may explain some observations describing poor vaccine response (e.g. Hepatitis B virus, not limited to SARS-CoV-2) [6], faster waning of antibodies [13], decreased ability to clear the virus [14], and higher rates of COVID-related death in this high risk population as observed in this study. Furthermore, current recommendations are that specific immunocompromised populations routinely receive additional doses [15]; it is unknown whether specific subgroups of dialysis patients could benefit from a similar response and mitigate number of and/or increased severity of infections in vaccinated patients on dialysis.…”
supporting
confidence: 53%
“…Beyond the surge of cases and the infrastructure limits of the dialysis units, the prolonged viral shedding measured by RT-PCR on nasopharyngeal swabs is appraised as a further cause of workplace stress because it tends to increase the cumulative number of cases requiring quarantine [ 2 ].…”
mentioning
confidence: 99%